A review on sensible heat based packed bed solar thermal energy storage system for low temperature applications. (1st September 2020) - Gautam, Abhishek; Saini, R.P.
Abstract: Solar thermal energy is one of the categories of renewable energy source and it is quantitative abundant and qualitative superior. It is capable to fulfil the global thermal energy demand and it emerges as a competitive option with the conventional equipment's if these systems are incorporated with storage units. The solar thermal storage unit can also improve the equipment performance in terms of a smooth supply of energy with fluctuated solar energy collection as solar radiation varies throughout a day. Packed bed storage system is one of the feasible techniques to store the solar thermal energy which can be assembled with various solar thermal applications of low temperature as well as high temperature. The present review covers the sensible heat based packed bed solar thermal energy storage systems for low temperature applications. It includes a brief discussion about packed bed, its thermodynamic background, temperature distribution within packed bed, various design parameters affecting its performance and its analysis based on the energy as well as exergy efficiency. Various experimental and numerical investigations for performance analysis of PBSS have also been reported. The economic feasibility of the PBSS and comparison of sensible heat based PBSS with latent heat based PBSS has also been discussed in detail.